POPULUS L. IN PROTECTIVE FORESTS OF LUHANSK REGION - Vysotska, N. Yu.; Yurchenko, V.A. (Forestry and Forest Melioration, 2018)
Introduction Case studies from around the world illustrate the economic, social, cultural and environmental impacts that poplars have on food security, poverty alleviation and sustainable land use. Sustainable agriculture is currently vulnerable in Lugansk Region. The region’s south-eastern part belongs to the crisis ecological zone as a result of the excessive technogenic load. Inasmuch as the poplars stands had mainly protective functions in Luhansk Region, it is necessary to analyze and systematize data on the current state of protective forests as well as on the poplars species diversity. It is also necessary to identify the most favourable conditions for poplars to spread as well as which conditions account for their getting considerably weakened. This will enable researchers to work out effective measures aimed at improving sustainability of poplar stands and enhancing their protective functions. The aim of the research was to discover peculiarities in spreading, growth and biological stability of the Populus species in protective stands of different purposes in the Luhansk Region conditions. Materials and Methods The stock volume and age structure of poplar stands were analyzed in different typological growing conditions in Luhansk Region. To do that, we used the comprehensive analysis of the data in the electronic subcompartment database of Ukrderzhlisproekt Production Association as of 01.01.2011, as well as the mathematical processing of the data obtained in 21 forest plots in State Enterprises “Luhanska Meliorative Research Station”, “Novoaydarske Forest and Hunting Economy”, “Bilovodske Forest and Hunting Economy“, “Kremіnske Forest and Hunting Economy“ and “Bіlokurakynske Forest and Hunting Economy”. The analysis was carried out for protective forests whose key figure denotes how they perform the environmental protection function.In total, we have analyzed over 1,800 subcompartments where poplars are the main species and make the first tree layer. The poplar stands were divided into several health condition category groups based on several visual characteristics (crown density and colour, the presence and proportion of dead branches in the crown, etc.) according to “Sanitary rules in the forests of Ukraine” (1995). Each tree was referred to one of six health condition categories (1st – healthy; 2nd – weakened; 3rd – severely weakened; 4th – drying up; 5th – recently died; 6th–died over a year ago). Health condition index (HCI) for forest stand was calculated as weighted average from trees number in each category of health condition. Results Poplar stands are mainly concentrated in the anti-erosion forests (51.5 %) and in the forests of the 1st and 2nd sanitary-protection zones of water sources (48 %). Populus nigra L. and P. deltoides Marsh. are most often to occur here – 44 % and 30 %, respectively. P. alba L. covers 428.6 ha (16 %), P. nigra var. pyramidalis Spach, P. laurifolia Ledeb. and P. balsamifera L. grow in small areas – 33.3 ha (1%), 10.5 ha (0.4%) and 4.8 ha (0.2%). Poplar mostly grows in fresh fertile site (24.4 %) and moist fertile site (22.4 %) conditions. A very small area of poplar stands is dry and fresh infertile pine sites (0.1 and 11.9 %, respectively), and dry, fresh and moist fairly infertile pine sites (1.2; 6.5 and 2.5 %, respectively). The macrocomplex of black poplar habitat is represented by a wide variety of typological spectrum. Conclusions In Luhansk Region, the average age of poplar forest stands is 50 years. At that, only 46.8% of poplar stands grow in optimal forest site conditions. The trees that are older than 50, have high mortality rate. To conclude, today’s health condition of the protective poplar forests points at the necessity to take proper forestry measures, such as salvage/sanitation cutting, reconstruction of the stands and increase of nutrition area for certain trees. 4 Tables, 14 Refs.